Bad moon rising? The Influence of the lunar cycle on amphibian roadkills - Mestre, Frederico (2020)
Annually, roads, and their associated users, are responsible for millions of roadkills worldwide. Mortality affects multiple taxonomic groups, but amphibians are particularly vulnerable, due to their size and underreporting. In fact, very high mortality frequencies can occur, mostly during short periods of time, when individuals migrate to and from reproduction areas (e.g., ponds). In this study, we assess the influence of the lunar cycle on amphibian roadkills, while accounting for weather conditions. As expected, the main environmental effects explaining roadkill numbers were weather related, with increases in minimum air temperature, average relative air humidity, and cumulative rainfall during the previous 24 h having a positive effect on roadkill numbers for all studied species. However, the lunar cycle also affected roadkills for two of the studied species. Darker nights had higher numbers of roadkills of Pleurodeles waltl, while moonlit nights had higher numbers of Salamandra salamandra. As such, these moon effects are species specific. Animals that are more active in moonlight may be at an advantage if their visual acuity is better than that of their predators. We hypothesize that differences between species in the response to moonlight may be due to differences perceived in predation risk. This information should be considered when designing mitigation measures. Volunteer actions, for instance, can be planned and coordinated keeping in mind the most appropriate weather conditions for the general amphibian community and specific phases of the lunar cycle for particular species.